Predictive Utility of Type and Duration of Symptoms at Initial Presentation in Patients with Mild Cognitive Impairment - Devier, Deidre J. (S. Karger AG, 2010)
BACKGROUND/AIMS: To assess (1) the duration and symptoms present in participants with mild cognitive impairment (MCI) and (2) the impact of these variables on predicting conversion to Alzheimer's disease (AD). METHODS: Participants with MCI (n = 148) were assessed and followed systematically. RESULTS: Decline in memory was reported as the first symptom in 118 of the cases. Converters had more symptoms (e.g. language decline, depression), and the combination of decline in memory and in performance of high-order social/cognitive activities as well as disorientation more often than nonconverters (p = 0.036). In an age-stratified Cox model, predictors of conversion to AD were shorter time since onset of memory decline and lower baseline MMSE score. CONCLUSIONS: Recent onset of memory decline with older age, decreased MMSE score, change in performance and disorientation indicate a greater likelihood of short-term conversion to AD. Copyright © 2010 S. Karger AG, Basel